2004
DOI: 10.1111/j.1444-2906.2004.00866.x
|View full text |Cite
|
Sign up to set email alerts
|

Reproductive biology of the female Japanese mantis shrimp Oratosquilla oratoria (Stomatopoda) in relation to changes in the seasonal pattern of larval occurrence in Tokyo Bay, Japan

Abstract: The reproductive traits and the monthly larval abundance of the mantis shrimp Oratosquilla oratoria were investigated in Tokyo Bay, Japan, in 2002.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
56
0
1

Year Published

2006
2006
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 44 publications
(59 citation statements)
references
References 19 publications
(44 reference statements)
2
56
0
1
Order By: Relevance
“…Therefore, the temporal activity of the cement glands could be considered as a secondary sexual character useful for establishing the spawning season of S. mantis. On the other hand, our histological observations suggest a synchronous development of oocytes into the S. mantis ovary, where almost all oocytes are extruded simultaneously, as already observed in other stomatopods (Kodama et al 2004). Do Chi (1975) reported that each female lays a single batch of eggs giving rise to a single generation per year.…”
Section: Discussionsupporting
confidence: 81%
“…Therefore, the temporal activity of the cement glands could be considered as a secondary sexual character useful for establishing the spawning season of S. mantis. On the other hand, our histological observations suggest a synchronous development of oocytes into the S. mantis ovary, where almost all oocytes are extruded simultaneously, as already observed in other stomatopods (Kodama et al 2004). Do Chi (1975) reported that each female lays a single batch of eggs giving rise to a single generation per year.…”
Section: Discussionsupporting
confidence: 81%
“…3a). This result suggests that the major spawning currently takes place in the summer, whereas primary spawning used to occur in the spring, at least during the 1950s to 1980s (Shimizu 2002, Kodama et al 2004, 2006c. Our calculation also showed that individuals currently derived from small spawners constituted 84% of the total recruitment.…”
Section: Discussionmentioning
confidence: 60%
“…The first seasonal peak of current spawning is primarily composed of females ≥10 cm in body length (from the base of the rostrum to the anterior edge of the median notch of the telson) and a few smaller females, whereas the second peak is dominated by smaller females (Kodama et al 2004). Small, sexually mature females (<10 cm) were first observed in the 1980s , and their proportion has since increased (Kodama et al 2004). Changes in O. oratoria life history and the body-length structure of landings over the past few decades are summarized in Table 1.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Its spawning season lasts from April to September. There are 2 spawning peaks for the population in Tokyo Bay: the early spawning season in May by large females of body length (BL) ≥ 10 cm (≥ 1 yr) and the late spawning season in August by small females of 7 ≤ BL < 10 cm (0-1 yr; Kodama et al 2004Kodama et al , 2006a) (BL is measured from the base of the rostrum to the anterior edge of the median notch of the telson). The spawning ground of O. oratoria is located in the southern part of the bay (below the line between the Tama River and Sodegaura; Ohtomi & Shimizu 1991; see Fig.…”
Section: General Life History Traits Of Oratosquilla Oratoriamentioning
confidence: 99%